Extended PC-104 to Acquire Satellite Housekeeping Data Based On Atmega32 - Ahmad Fauzi (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2016)
PC-104 Standard is widely used in satellite spacecraft because of its rugged and robust. OBDH (On Board Data Handling) in our design uses PC-104 standard. To fulfill the OBDH requirement in gathering the housekeeping data, extended PC-104 is needed to be designed. To design the extended PC104, Proteus software was used initially to simulate the electronic circuit application. In the Proteus Design, electronic circuit and components was created. The temperature sensor and voltage sensor was included to produce a precision data. To know the data value, LCD (Liquid Crystal Display) component was used to display the data value. It showed that the current sensor has a linear data with an average accuracy of 1.1 %. The final result in this research is extended PC-104 has been designed and ready to be implemented in to the real device.